Mysterious locations in the fantastic literature of Aragon, during the 19th century - Vega Guardia, Ángel (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
The article analyzes the influence could have exerted the geographical area on numerous Spanish authors of the 19th century in terms of fantastic literature in Aragon, and that which borders with notions like human alienation or madness. A rich list of novels and short stories will be reviewed in detail, taking into account both the inherent components of the genre that deals with the world of fear, the strange, the unexpected, the subversive and often the inexplicable, as well as the ascendancy that was professed in all this by the geographical locations in all its aspects, as well as the cultural, historical, artistic and spiritual elements.
Keywords: Fantastic Literature; Aragon in the nineteen-century literature; Geography; History